Rodney and the rusties - Egan, Kate. (New York : HarperKidsEntertainment, 2005)
"When Rodney gets to Robot City, he is far from home and very lonely. Luckily, Rodney soon meets the Rusties, a ragtag group of friends who become his new family. Follow Rodney and the Rusties on their exciting adventures!"--Cover back.
Based on the original motion picture, Robots.
Keywords: Robots -- Fiction